Zoneamento ambiental e funcional do baixo curso do Rio Cacheu/Guiné-Bissau: subsídios ao planejamento territorial - Correia Junior, Antonio (2018)
There is now increasing biodiversity degradation at different scales of analysis, interfering with global, regional and local environmental dynamics, including environmental systems in the coastal and coastal regions of Guinea-Bissau, mainly due to the abuse of natural resources and destruction of ecosystems. It is here to instigate an analysis by incorporating needs and care into the society-nature relationship in the face of the quest to satisfy individual human needs and their eagerness for power. In this context, this research aimed to provide subsidies for the implementation and development of actions directed towards the management of coastal resources management. The specific objectives were: i) to identify the problems and the current situation of the occupation of the coastal region of Cacheu; ii) to study the cultural manifestations and the main traditional practices of subsistence of the communities; iii) research on the limitations, problems and socio-environmental potential of the Cacheu region; and iv) propose a set of actions to be included in a plan for integrated environmental planning and management that will trigger local sustainability. The methodological procedures of the research were based on discussions and theoretical studies of geosystemic analysis, through the collection of secondary data, bibliographic review, interpretation of satellite images, cartographic collections and field work. These stages allowed us to understand the dynamics of the areas that remained with natural vegetation and those in which human exploration took place over time. In view of the above, it was found that the natural landscape of the Lower Course of the Cacheu River presents as a strongly modified environment, where primary vegetation was almost completely replaced by secondary ecological successions, due to human degrading action. The study area is considered as an ecosystem subject to drastic environmental impacts, the vegetation being seriously threatened by the inadequate use of the soil, and it is necessary to promote specialized studies capable of leading to sustainable development. In this sense, there were many problems in the local environmental units, such as inadequate disposal of solid waste, lack of basic sanitation, disordered occupation, among others. These problems occur due to non-compliance, lack of solid waste management, lack of environmental perceptions of the local community, lack of management plan or lack of effective actions by the State.